(untitled) (Annual of the Faculty of Philosophy in Skopje, 2011)
There are only few genitive singular forms of stems ending in stops on Mycenaean tablets. Still the analysis of the examples shows that in the Mycenaean period, the genitive singular of stems ending in stops already had the characteristics typical for the Greek language in respect of the ending and the root or suffix ablaut grade. On the other hand, the examples present archaic aspects - words that disappeared in the post-Mycenaean period and peculiarities in respect of semantics and word formation.